Clinical importance of cytokine (IL-6, IL-8, and IL-10) and vitamin D levels among patients with Type-1 diabetes - Azharuddin Sajid Syed Khaja; Naif K. Binsaleh; Mirza Masroor Ali Beg; Fauzia Ashfaq; Mohammad Idreesh Khan; Malak Ghazi Almutairi; Husam Qanash; Mohd Saleem; Ibrahim Abdelmageed Mohamed Ginawi (Scientific Reports)
Abstract Type-1 diabetes (T1D) is an autoimmune disorder characterized by impaired insulin release by islet β cells. It has been shown that proinflammatory cytokines released during the disease can exacerbate the condition, while anti-inflammatory cytokines offer protection. This study analyzed the clinical role of interleukin (IL)-6, -8, -10, and vitamin D levels in T1D patients compared to healthy controls. The levels of IL-6, IL-8, IL-10, and vitamin D in the participants’ serum samples were analyzed using ELISA. The findings showed that T1D patients had significantly increased levels (p < 0.0001) of fasting blood glucose, HbA1c, systolic blood pressure, low-density lipoprotein, triglycerides, cholesterol, and very low-density lipoprotein and decreased levels of high-density lipoprotein and vitamin D (p < 0.0001) compared to healthy controls. Moreover, the levels of IL-6, IL-8, and IL-10 were also significantly greater (p < 0.0001) in T1D patients. The study also determined the significance of these cytokines among T1D patients and healthy controls using ROC curves. Furthermore, we found that smokers had significantly higher levels of IL-6 (p = 0.01) and IL-8 (p = 0.003) than non-smokers. These results showed that elevated levels of IL-6, IL-8, and IL-10, decreased vitamin D levels, and smoking among T1D participants could contribute to the worsening of T1D disease and could serve as predictive indicators.